The WW‐FINGERS‐SARS‐CoV2 initiative: Impact of the COVID‐19 pandemic on brain health and prevention strategies - Mangialasche, Francesca; Pérez, Kristal Morales; Lehtisalo, Jenni; Solomon, Alina; Peltonen, Markku; Ngandu, Tiia; Kivipelto, Miia (ALZHEIMERS & DEMENTIA, 2021)
Background Older adults have higher risk of cognitive impairment and dementia, and they also represent the group most severely affected by the SARS‐CoV‐2 (COVID‐19) pandemic in terms of higher morbidity and mortality. The World‐Wide FINGERS (WW‐FINGERS) global network of multidomain trials for dementia risk reduction and prevention (Kivipelto et al., 2020) provides a unique framework to explore how the pandemic has affected factors related to mental and physical health of populations at increased risk of dementia, while accounting also for country‐specific strategies to contain the spread of the infection. Methods The WW‐FINGERS‐SARS‐CoV2 survey has been developed to explore direct and indirect effects of the pandemic in midlife and older age. The questions aim to measure changes in lifestyle factors (e.g., diet, physical activity), management of chronic noncommunicable diseases (e.g., diabetes, hypertension), as well as psychosocial factors ‐ including depressive symptoms, sleep disorders, social isolation ‐ that are relevant to cognition and are expected to be affected by the pandemic. The survey measures also established and possible epidemiologic risk factors for severe COVID‐19. To facilitate distribution is different settings, both a pen‐and‐paper and a digital version of the survey have been developed in several languages. The digital version is supported through REDCap (Research Electronic Data Capture), a secure web‐based software that is being also used for harmonized data collection. Results Over 25 countries are taking part in the survey. Local adaptations and piloting are being done to optimize implementation in both clinical‐based and population‐based settings. Participants are in the at‐risk spectrum for dementia: from cognitively normal persons to individuals with pre‐dementia cognitive symptoms. An updated report of the survey status will be presented. Conclusion the survey is a joint global action of the WW‐FINGERS network which can inform better care of older adults in the context of a pandemic. The survey is also a valuable tool for pre‐screening of participants for prevention trials, and results can inform adaptions to ensure successful recruitment and adherence in forthcoming multidomain trials for dementia prevention in older adults.